2020
DOI: 10.4103/sja.sja_760_19
|View full text |Cite
|
Sign up to set email alerts
|

Floppy epiglottis together with extra-laryngeal mass causing an inducible laryngeal obstruction and hypoxemic event in an adult: A case report

Abstract: Floppy epiglottis in an adult is rare and often pathological. Airway obstruction caused by floppy epiglottis in an adult is rarely reported. Neck mass, however, can affect the airway in many ways; however, inducible upper airway obstruction by extra-laryngeal neck mass is hardly been reported. In most of the instances of inducible laryngeal obstruction, the tumor is found in and around the laryngeal inlet. Herein, we report such an unusual incident happened to a 40-year-old gentleman, a case of oral carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A total of 33 studies were included in our review 9‐11,19‐48 . A PRISMA diagram outlining our search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 33 studies were included in our review 9‐11,19‐48 . A PRISMA diagram outlining our search is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…One study suggests that their patient's symptoms correlate with cases of ALM reported in the literature 25 . One study references ALM, but instead describes their patient as having “inducible laryngeal obstruction.” 33 Finally, Templer et al was the earliest description of this entity and does not use the term ALM specifically, but they do refer to similarities with congenital laryngomalacia in their discussion 9 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation